Core‐Shell Nanofibers of Polyvinyl Alcohol/Polylactic Acid Containing TiO2 Nanotubes for Natural Sunlight Driven Photocatalysis. Issue 2 (23rd November 2021) - Ponnamma, Deepalekshmi; Elgawady, Yara; Nair, Sabari S.; Hassan, Mohammad K.; Al‐Maadeed, Mariam Al Ali
Abstract: Highly stable and efficient coaxial electrospun fibers of polyvinyl alcohol (PVA) and polylactic acid (PLA) nanocomposite filled with titanium dioxide (TiO2 ) nanotubes areaccomplished for natural sunlight‐driven photocatalytic dye degradation. The coaxial electrospinning process generates well‐defined concentric cylinder‐like morphology, with the polymeric core and sheath phases, with TiO2 present only in the outer phases. The nanofibers are characterized for their coaxial morphology and the distribution of TiO2 in the sample is monitored through EDAX studies. Coaxial electrospinning process influences the polymeric structural and functional performances, regulates the crystallization kinetics, and ensures the entanglement of TiO2 nanopowders without allowing them to leach out. Photodecomposition of Rhodamine B and methylene blue dye are observed by the UV–visible studies and ≈80% and ≈85% degradation is achieved respectively after 8 h. A higher efficiency of degradation is achieved for the TiO2 nanocomposites, due to the photocatalytic activity of the TiO2 semiconductors, and also because of its presence in the sheath phase. The efficiency of dye degradation is correlated with the mechanical and dynamic mechanical properties of the fibers and with the typical fiber morphology and spinning mechanism. While the dye molecules get trapped in the porous sites of composite fibers, the TiO2 radicals initiates the photocatalysis process. The current technology is promising in manipulating flexible, durable, and environmentally friendly polymer nanocomposite fibers for industrial wastewater purification. Abstract : Core shell nanofibers of PVA and PLA polymer decorated with TiO2 nanotubes on the outer layer improve the photocatalytic degradation efficiency towards methylene blue and Rhodamine B dyes. In 8 h, the PLA‐TiO2 /PVA fibers disintegrated the organic molecules with a photocatalytic efficiency of 85%. The significance of this research includes natural sunlight driven degradation and absence of any secondary pollution.